1997
DOI: 10.1364/ao.36.004562
|View full text |Cite
|
Sign up to set email alerts
|

Angular correlation function of speckle patterns scattered from a one-dimensional rough dielectric film on a glass substrate

Abstract: We present the experimental results of the angular correlation function of far-field speckle patterns scattered by a one-dimensionally random rough surface of a thin dielectric film on a glass substrate when a polarized beam of light is incident upon the rough surface from vacuum. This surface, which separates the vacuum and the dielectric, is rough enough that only diffused speckles are observed. The experiment for the correlation measurement was set up to make use of a CCD camera to obtain the image of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…If we have one scattered speckle intensity 1(8 ,O Si) observed at the scattering angle e sl generated by an incident light at angle of incidence of 0 and another scattered speckle intensity 1(0 j2 s2 ) observed at the scattering angle 0 s2 generated by an incident light at angle of incidence of 0 j2 the normalized angular correlation between them is defined by: (1) [(< I(O,O)2 > < I(O,e) >2)(< I(0j2,052)2 > < I(0i2,0S2) >2)]2 the <.. .> denotes ensemble averaging among the speckles of the speckle distribution. It has been shown that a strong correlation can be observed if the following conditions are satisfied: (8) sin 0 -sinO = sinO i2 sinO s2 .…”
Section: Angular Correlation Functionmentioning
confidence: 99%
“…If we have one scattered speckle intensity 1(8 ,O Si) observed at the scattering angle e sl generated by an incident light at angle of incidence of 0 and another scattered speckle intensity 1(0 j2 s2 ) observed at the scattering angle 0 s2 generated by an incident light at angle of incidence of 0 j2 the normalized angular correlation between them is defined by: (1) [(< I(O,O)2 > < I(O,e) >2)(< I(0j2,052)2 > < I(0i2,0S2) >2)]2 the <.. .> denotes ensemble averaging among the speckles of the speckle distribution. It has been shown that a strong correlation can be observed if the following conditions are satisfied: (8) sin 0 -sinO = sinO i2 sinO s2 .…”
Section: Angular Correlation Functionmentioning
confidence: 99%
“…The speckle pattern is obtained by direct illumination of the CCD camera, without the use of an optical objective. This approach experimentally differs from previous similar experiments [9,10]. As summarized in [14], every pixel composing the speckle pattern in our case is an average of scattering contributions from all the surface elements illuminated by the laser.…”
Section: Set-up a 10mwmentioning
confidence: 82%
“…3 Results and discussion When a first speckle pattern I(θ i1 ,θ s1 ) is recorded using illumination and observation angles θ i1 and θ s1 respectively, its correlation coefficient with a second image I(θ i2 ,θ s2 ) obtained for angles θ i2 and θ s2 is given by [9]: …”
Section: Set-up a 10mwmentioning
confidence: 99%
See 1 more Smart Citation
“…These phenomena have now been confirmed theoretically and experimentally for volume scattering [2-81. Correlation in light scattering from random rough surfaces has also been studied [9-141. Taking into account multiple scattering, the intensity correlation function for light elastically scattered from a randomly rough metallic grating was calculated [9] and the angular correlation function of speckle patterns scattered from a one-dimensional (ID) rough dielectric film on a glass substrate was investigated [14]. Recent theoretical analysis of the angular intensity correlation function in the double passage of waves through a random phase screen has been carried out by Escamilla er a1 [ 151.…”
Section: Introductionmentioning
confidence: 99%